Genetic polymorphisms and metabolism of endocrine disruptors in cancer susceptibility - Ana Hatagima
Epidemiological studies have estimated that approximately 80% of all cancers are related to environmental factors. Individual cancer susceptibility can be the result of several host factors, including differences in metabolism, DNA repair, altered expression of tumor suppressor genes and proto-oncogenes, and nutritional status. Xenobiotic metabolism is the principal mechanism for maintaining homeostasis during the body's exposure to xenobiotics. The balance of xenobiotic absorption and elimination rates in metabolism can be important in the prevention of DNA damage by chemical carcinogens. Thus the ability to metabolize and eliminate xenobiotics can be considered one of the body's first protective mechanisms. Variability in individual metabolism has been related to the enzymatic polymorphisms involved in activation and detoxification of chemical carcinogens. This paper is a contemporary literature review on genetic polymorphisms involved in the metabolism of endocrine disruptors potentially related to cancer development.